Effect Of Balancing Funds And Special Autonomy Funds On Economic Growth In West Papua Province (Capital Expenditure As An Intervening Variable) - Marthen Anthon Pentury (Jurusan Ilmu Ekonomi dan Studi Pembangunan Universitas Jenderal Soedirman, 2020)
Economic growth in West Papua Province is intensively carried out in order to pursue better economic development compared to other regions. The impetus for regional development comes from the central government transfer namely the balance fund and the special autonomy fund. The purpose of this study was to analyze the magnitude of direct and indirect effects through intervening variables. The variables in this study are balance funds (X1), special autonomy funds (X2), capital expenditure (Z) as intervening variables and economic growth (Y). The data source comes from BPS. By using the path analysis regression method. The results showed that the balancing fund and special autonomy fund did not significantly influence capital expenditure, while the balancing fund, special autonomy fund and capital expenditure had a significant effect on economic growth. The indirect effect shows the insignificant influence of the balance fund and special autonomy fund through intervening variable capital expenditure on economic growth.Keywords : Balancing Funds, Special Autonomy Funds, Capital Expenditure and Economic Growth